Pelvic Fractures in Children Results from the German Pelvic Trauma Registry: A Cohort Study. Issue 51 (December 2015) - Zwingmann, Jörn; Aghayev, Emin; Südkamp, Norbert P.; Neumann, Mirjam; Bode, Gerrit; Stuby, Fabian; Schmal, Hagen
Abstract : Abstract: As pelvic fractures in children and adolescents are very rare, the surgical management is not well delineated nor are the postoperative complications. The aim of this study using the prospective data from German Pelvic Trauma Registry study was to evaluate the various treatment approaches compared to adults and delineated the differences in postoperative complications after pelvic injuries. Using the prospective pelvic trauma registry established by the German Society of Traumatology and the German Section of the Arbeitsgemeinschaft für Osteosynthesefragen (AO), International in 1991, patients with pelvic fractures over a 12-year time frame submitted by any 1 of the 23 member level I trauma centers were reviewed. We identified a total of 13, 525 patients including pelvic fractures in 13, 317 adults and 208 children aged ≤14 years and compared these 2 groups. The 2 groups' Injury Severitiy Score (ISS) did not differ statistically. Lethality in the pediatric group was 6.3%, not statistically different from the adults' 4.6%. In all, 18.3% of the pediatric pelvic fractures were treated surgically as compared to 22.7% in the adult group. No child suffered any thrombosis/embolism, acute respiratory distress syndrome (ARDS), multiorgan failure (MOF), or neurologic deficit, nor was any septic MOF detected. The differences between adults and children were statistically significant in that the children suffered less frequently from thrombosis/embolism ( P = 0.041) and ARDS and MOF ( P = 0.006). This prospective multicenter study addressing patients with pelvic fractures reveals that the risk for a thrombosis/embolism, ARDS, and MOF is significant lower in pediatric patients than in adults. No statistical differences could be found in the ratios of operative therapy of the pelvic fractures in children compared to adults.